Gender difference and career interest among undergraduates: Implications for career choices - AlMiskry, Abdullah Seif; Bakar, Ab. Rahim; Mohamed, Othman (European Journal of Social Sciences, 2009)
A study was conducted to determine the career interests of university students. Two hundred and thirty-eight undergraduates were involved in the study. They consisted of 101 male and 137 female students attending three public universities in Malaysia. There was a significant different of realistic career interest pattern between male and female students.